RESIDENSE TIME EFFECTS ON THE NOX REMOVAL EFFICIENCY IN TWO DIFFERENT DIELECTRIC BARRIER DISCHARGE CELL - E. León del Villar (Tecnología Química, 2010)
Experimental tests of the removal of NOx compounds were carried out in two dielectric barrierdischarge cells (DBD) reactors at Physics plasma laboratory of Mexico Nuclear center Twodifferent geometries of these reactor were studied, one circular 11.94 cm diameter, and anotherrectangular,16x7 cm, both 2.5 mm gap and 28.0 cm3 reaction volumeA gas mixture composed of 1.0 l/m of molecular nitrogen was injected to each reactor along withan additional flow that provided a concentration of 90 ppm of NO in both cells. The gas mixturewas treated with non – thermal plasma generated by dielectric barrier discharge at differentworking potentials and at a 1.75 kHz frequency. The residual products were identified by meansof a Sensonic 2000 gas analyzer..According to the experimental results, it was identified a greater removal efficiency in therectangular cell than in the circular one. This might be attributed both to residence time due togeometric effects and to a factor related with the chemical reaction mechanisms, since it has beenshowed that, at greater powers, the removal efficiency diminishes due to the regeneration of NOby inverse kinetic mechanisms. Our kinetic model proves that the main reaction product was N2Oin the presence of a reducing atmosphere.